2012
DOI: 10.32398/cjhp.v10isi-obesity.1466
|View full text |Cite
|
Sign up to set email alerts
|

Creating Playgrounds, Where Playgrounds Do Not Exist

Abstract: Recent emphasis has been placed on the effect the built environment has on physical activity levels of children. Children living in poorly planned or urban neighborhoods (areas with limited room or green space for play, lack of sidewalks and streets that do not connect) have less access to physical activity opportunities. The purpose of this article is to describe a shared venture between a public university, nonprofit organization and faith based organization to increase physical activity among children livin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Play Streets ( n = 19) included in study were held for at least 7 consecutive days from 2 to 7 pm in July and/or Aug. 2013 (Play Streets could happen a max of 14 total days in July and/or Aug., consecutive or not). 3 volunteers mandatory/Play Street, could “hire” for free a box of play equipment from city council, other play materials, hire an organized activity by city council, or organize activities themselves.Play Streets-style intervention with temporary closure of a street or parking lot McGlone (2016) [22]Melbourne, Australia (Albert Park: affluent suburb of Melbourne) Pop-up Park usersSemi-structured Child interviews n = 20) Focus groups: children n = 9, adults n = 7Child interviews: 5–12 yrs.Child interviews: 75% female ( n = 15) Focus groups: child 77.8% female (n = 7), adults 100% female (n = 7); local residents and staff of Albert Park Primary SchoolCross-sectional: teacher semi-structured interviews; 2 focus groups (adult and child)Pop-up Park: 12–24 month trial (beginning July 2013) of a pop-up Park near a primary school, open at all times to the general public. Espinoza et al (2012) [42]Santa Ana, CASpecific neighborhood (92,701 zip code of Santa Ana, CA) that lacked access to indoor recreation, exercise facility, or outdoor play area (> 70% lived ≥20 min from one of these locations).N = 24 families with children ages 6–14 yrsChildren: 53% were 6–10 yrsChildren: 53% male; 84% Latino/Hispanic; 92% annual income < $30,000; 88% lived in an apartmentCross-sectional: non-random area samplingMobile Physical Activity Unit (MPAU): Abandoned bus was renovated and filled with playground equipment to create a MPAU, which was intended to “bring the playground” to participating families and allow children an opportunity to play in a safe and supervised environment. MPAU driven to a single school every Tuesday evening from 4 pm–6 pm and Saturday mornings from 10 am-12 pm for a total of 12 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Play Streets ( n = 19) included in study were held for at least 7 consecutive days from 2 to 7 pm in July and/or Aug. 2013 (Play Streets could happen a max of 14 total days in July and/or Aug., consecutive or not). 3 volunteers mandatory/Play Street, could “hire” for free a box of play equipment from city council, other play materials, hire an organized activity by city council, or organize activities themselves.Play Streets-style intervention with temporary closure of a street or parking lot McGlone (2016) [22]Melbourne, Australia (Albert Park: affluent suburb of Melbourne) Pop-up Park usersSemi-structured Child interviews n = 20) Focus groups: children n = 9, adults n = 7Child interviews: 5–12 yrs.Child interviews: 75% female ( n = 15) Focus groups: child 77.8% female (n = 7), adults 100% female (n = 7); local residents and staff of Albert Park Primary SchoolCross-sectional: teacher semi-structured interviews; 2 focus groups (adult and child)Pop-up Park: 12–24 month trial (beginning July 2013) of a pop-up Park near a primary school, open at all times to the general public. Espinoza et al (2012) [42]Santa Ana, CASpecific neighborhood (92,701 zip code of Santa Ana, CA) that lacked access to indoor recreation, exercise facility, or outdoor play area (> 70% lived ≥20 min from one of these locations).N = 24 families with children ages 6–14 yrsChildren: 53% were 6–10 yrsChildren: 53% male; 84% Latino/Hispanic; 92% annual income < $30,000; 88% lived in an apartmentCross-sectional: non-random area samplingMobile Physical Activity Unit (MPAU): Abandoned bus was renovated and filled with playground equipment to create a MPAU, which was intended to “bring the playground” to participating families and allow children an opportunity to play in a safe and supervised environment. MPAU driven to a single school every Tuesday evening from 4 pm–6 pm and Saturday mornings from 10 am-12 pm for a total of 12 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Adult opinion: temporary space provided respite for some children and fostered creativity given lack of structure.NRChild Focus Group: Increased connection to the community was expressed; few expressed negative response by residents, although some conflict was experienced; pop-up park provided a different view of public life than other places. Child & Adult focus groups: all viewed space as fairly to very important to the local community due to need for more gathering space or children’s enjoyment of having contact with other people in community. Espinoza et al (2012) [42]Baseline data collected via questionnaire administered in the home (and in Spanish), along with informal feedback collected from children and parents before, during, and after 12-week intervention period, to document barriers, aesthetics, proximity and availability of parks, open spaces or green belts in the 92,701 zip code, and the time it takes to walk to the nearest PA amenity. Daily attendance logs were collected to document children’s utilization of the MPAU.Overall attendance was NR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have evaluated how environmental interventions at a community level affect outdoor play and children’s PA. Farley et al [ 25 ] found that in a neighborhood that provided supervised schoolyards with improved equipment that opened after school hours there were 30% more active children in comparison to the number of active children in areas without these conditions. Similarly, high attendance rates were reported when pop-up parks with age-appropriate activities were implemented in parking lots [ 26 ]. Conversely, during programs in which children were encouraged to participate in outdoor activities without corresponding changes to the environment, the participation rates were low [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, high attendance rates were reported when pop-up parks with age-appropriate activities were implemented in parking lots [26]. Conversely, during programs in which children were encouraged to participate in outdoor activities without corresponding changes to the environment, the participation rates were low [27].…”
Section: Introductionmentioning
confidence: 99%